Animated Video “Dare to Dream”: Media Development in Enhancing Children's Creativity - Veryawan, Veryawan; Syahputra, Hermawan; Sriadhi, Sriadhi; Mahyuni, Mahyuni (PT. Technology Laboratories Indonesia (TechnoLabs), 2025)
This study aims to determine the feasibility of developing the “Dare to Dream” animated video interactive learning media in enhancing creativity in early childhood. The research method used is Research and Development (R&D) with the ADDIE model, which consists of five stages: Analysis, Design, Development, Implementation, and Evaluation. The concept of the animated video is to introduce various professions. After watching, children will be invited to role-play with their classmates with the aim of enhancing creativity. The subjects of this development study were media validators, material validators, language validators, and early childhood children. The results of the media expert validation showed a percentage of 87% in the “highly feasible” category. The results of the material validation obtained a percentage of 85% with a category of “very feasible”. The results of the language expert validation obtained a percentage of 90% with a category of “very feasible”. Then, the results of the trial with children obtained a category of very feasible or very effective with a percentage of 92%. Based on this research, it can be concluded that the animated video media “Dare to Dream” is very feasible and effective for increasing the creativity of early childhood.